Uhl's Disease: an Uncommon Presentation of a Rare Disease - Aguiar Rosa, S (2018)
Uhl's disease, also known as Uhl anomaly, is a rare disease secondary to selective but uncontrolled apoptosis of right ventricular myocytes during the perinatal period, after complete cardiac development, leading to the absence of right ventricular myocardium and the direct apposition of endocardium to epicardium without a myocardial layer in between, resulting in right ventricular failure. The present paper describes a case of Uhl's disease with an uncommon presentation. A 28-year-old man was admitted with dyspnea and cyanosis. Transthoracic echocardiography showed severe dilation of the right chambers, impaired right ventricular systolic function and a large ostium secundum atrial septal defect (ASD). Cardiac catheterization revealed pulmonary hypertension, with increased pulmonary capillary wedge pressure (mean 19mmHg) and Qp:QS 0.88:1. At this point, the authors considered that a main diagnosis of ASD could not explain the clinical features and hemodynamic data. A primary disease of the right ventricle was the most likely hypothesis and cardiac magnetic resonance imaging was performed, which demonstrated an extremely thin-walled right ventricle, with almost complete absence of right ventricular free wall myocardium, compatible with Uhl's disease.